Novel dual-regulators of Pseudomonas aeruginosa are essential for productive biofilms and virulence - Heacock-Kang, Yun (Mol Microbiol, 2018)
Gene regulation network in Pseudomonas aeruginosa is complex. With a relatively large genome (6.2 Mb), there is a significant portion of genes that are proven or predicted to be transcriptional regulators. Many of these regulators have been shown to play important roles in biofilm formation and maintenance. In this study, we present a novel transcriptional regulator, PA1226, which modulates biofilm formation and virulence in P. aeruginosa. Mutation in the gene encoding this regulator abolished the ability of P. aeruginosa to produce biofilms in vitro, without any effect on the planktonic growth. This regulator is also essential for the in vivo fitness and pathogenesis in both Drosophila melanogaster and BALB/c mouse lung infection models. Transcriptome analysis revealed that PA1226 regulates many essential virulence genes/pathways, including those involved in alginate, pili, and LPS biosynthesis. Genes/operons directly regulated by PA1226 and potential binding sequences were identified via ChIP-seq. Attempts to confirm the binding sequences by electrophoretic mobility shift assay led to the discovery of a co-regulator, PA1413, via co-immunoprecipitation assay. PA1226 and PA1413 were shown to bind collaboratively to the promoter regions of their regulons. A model is proposed, summarizing our finding on this novel dual regulation system.